2011
DOI: 10.1038/leu.2011.222
|View full text |Cite
|
Sign up to set email alerts
|

Human allo-reactive CD4+ T cells as strong mediators of anti-tumor immunity in NOD/scid mice engrafted with human acute lymphoblastic leukemia

Abstract: Adoptive immunotherapy with donor lymphocyte infusion (DLI) after allogeneic stem cell transplantation (alloSCT) may not only mediate Graft-versus-Leukemia (GvL) reactivity, but also induce Graft-versus-Host Disease (GvHD). As HLA-class II molecules are predominantly expressed on hematopoietic cells, CD4 þ T cells may selectively mediate GvL reactivity without GvHD. Here, we assessed the capacity of human CD4 þ T cells to act as sole mediators of GvL reactivity in a NOD/scid mouse model for human acute lymphob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…30,31 In addition to this, it was shown that alloreactive CD4 + T cells directed against mismatched HLA class II molecules were capable of directly eliminating leukemic cells in adult patients. 32 As many unit-recipient HLA class II mismatches were present, we hypothesize that HLA class II-specific CD4 + T cells of the ultimately surviving unit elicit an immediate and targeted alloreactive immune response towards mismatched HLA class II molecules of the nonengrafting unit in the absence of ATG. This hypothesis may be supported by the observation of a relatively rapid CD4 + T-cell recovery, by the abundance of class II mismatches, and also by the protracted presence of the nonengrafting unit in patients who had received a unit combination with a high inter-unit level of HLA matching.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 In addition to this, it was shown that alloreactive CD4 + T cells directed against mismatched HLA class II molecules were capable of directly eliminating leukemic cells in adult patients. 32 As many unit-recipient HLA class II mismatches were present, we hypothesize that HLA class II-specific CD4 + T cells of the ultimately surviving unit elicit an immediate and targeted alloreactive immune response towards mismatched HLA class II molecules of the nonengrafting unit in the absence of ATG. This hypothesis may be supported by the observation of a relatively rapid CD4 + T-cell recovery, by the abundance of class II mismatches, and also by the protracted presence of the nonengrafting unit in patients who had received a unit combination with a high inter-unit level of HLA matching.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by our study demonstrating that leukemic cells can acquire a professional APC phenotype in vivo upon interaction and release of proinflammatory cytokines by allo-reactive CD41 T cells. 46 Moreover, we previously demonstrated that not only AML blasts, 47,48 but also other leukemic cells, 46-50 upregulated expression of HLA, adhesion, and costimulatory molecules in the presence of soluble factors and acquired an enhanced capacity to stimulate allogeneic T cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by our study demonstrating that leukemic cells can acquire a professional APC phenotype in vivo upon interaction and release of proinflammatory cytokines by allo-reactive CD41 T cells. 46 Moreover, we previously demonstrated that not only AML blasts, 47,48 but also other leukemic cells, 46-50 upregulated expression of HLA, adhesion, and costimulatory molecules in the presence of soluble factors and acquired an enhanced capacity to stimulate allogeneic T cells in vitro.In summary, we showed in 2 patients that prophylactic CD41 DLI administered early after HLA-DPB1-mismatched TCD-alloSCT led to conversion to donor hematopoiesis with concomitant GVHD caused by allo-reactive CD41 T cells directed against patientmismatched HLA-DPB1 alleles. Our results suggest that active CMV infection and subsequent expansion and cytokine release by residual patient-derived CMV-specific T cells may have provided essential inflammatory triggers for development of GVHD by HLA-DPB1-specific CD41 T cells.…”
mentioning
confidence: 99%
“…[4][5][6][7] In a NOD/SCID mouse model for human acute lymphoblastic leukemia, infusion of human CD4 ϩ T cells led to eradication of the malignant cells. 8 Clinical trials in allogeneic stem cell transplantation (alloSCT) found that depletion of CD8 ϩ T cells from donor lymphocyte infusion preserved the ability of the T cells to induce conversion to donor chimerism, 9,10 highlighting the direct effector function of CD4 ϩ T cells.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] In a NOD/SCID mouse model for human acute lymphoblastic leukemia, infusion of human CD4 ϩ T cells led to eradication of the malignant cells. 8 Clinical trials in allogeneic stem cell transplantation (alloSCT) found that depletion of CD8 ϩ T cells from donor lymphocyte infusion preserved the ability of the T cells to induce conversion to donor chimerism, 9,10 highlighting the direct effector function of CD4 ϩ T cells.Antigen presentation to T cells by HLA surface molecules depends on protein degradation mediated by proteasomes and lysosomal proteases as the 2 major cellular breakdown mechanisms. Traditionally, it has been assumed that HLA class II molecules present exogenous antigens which are degraded by proteases within the endosomal/lysosomal system, whereas endogenous cytosolic antigens are degraded by the proteasome and presented by HLA class I molecules.…”
mentioning
confidence: 99%